(M, N)-exponential model in the theory of excitons - Piskovoi, V.N.; Strelniker, Ya.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
The one-exponential excitonic model, widely used in the theory of light propogation through spatially dispersive media, is generalized in order to take into account the simultaneous existing of M exciton states and N transport mechanisms. The physical reason and possibilities of the proposed model is demonstrated on the base of the Frenkel exciton. The model essentially extends the area of the possible applications consarving at the same time the exact solubilities and other advantages of the traditional exponential-like approches for the case of the bounded media. The model is used in the paper for deriving the balance equations of the energy density and the energy flux density as well as for studing of boundary value and some other crystal optics problems near the excitonic resonances.